2011
DOI: 10.1097/jto.0b013e31820b8b9b
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Elderly When Cure is the Goal: The Influence of Age on Treatment Selection and Efficacy for Stage III Non-small Cell Lung Cancer

Abstract: : In select fit elderly patients, combined modality therapy is tolerable and is associated with survival similar to that of younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…In our study, patients with a high BMI and aged < 54.5 experienced longer PFS, which indicates that advanced age might be a negative predictive factor of chemotherapy. A previous study reported that patients aged > 65 years were more likely to have poor performance status, multiple comorbidities, and survival rates became poorer with increasing age . The shorter PFS of older patients in our study might also be a result of poor performance status and a higher rate of comorbidities, although previous research has shown that age does not worsen efficacy or tolerance to NSCLC .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our study, patients with a high BMI and aged < 54.5 experienced longer PFS, which indicates that advanced age might be a negative predictive factor of chemotherapy. A previous study reported that patients aged > 65 years were more likely to have poor performance status, multiple comorbidities, and survival rates became poorer with increasing age . The shorter PFS of older patients in our study might also be a result of poor performance status and a higher rate of comorbidities, although previous research has shown that age does not worsen efficacy or tolerance to NSCLC .…”
Section: Discussioncontrasting
confidence: 55%
“…A previous study reported that patients aged > 65 years were more likely to have poor performance status, multiple comorbidities, and survival rates became poorer with increasing age. 27 The shorter PFS of older patients in our study might also be a result of poor performance status and a higher rate of comorbidities, although previous research has shown that age does not worsen efficacy or tolerance to NSCLC. 28 A larger cohort and multivariate analysis of the relationship between age and treatment efficacy are required.…”
Section: Discussionmentioning
confidence: 56%
“…Radiotherapy is a major therapeutic intervention for patients with lung cancer and is administered to up to 75% of lung cancer patients during the course of their disease (33). Prognosis for lung cancer patients remains poor, in part due to resistance to radiation or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is a major therapeutic intervention for patients with lung cancer and is administered to up to 75% of lung cancer patients during the course of their disease (50). A major challenge affecting outcomes of patients with lung cancer is the development of acquired radioresistance.…”
Section: Discussionmentioning
confidence: 99%